2023
DOI: 10.1002/ohn.173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Facility Type and Volume on Outcomes in Head and Neck Mucosal Melanoma

Abstract: Objective. To evaluate differences in treatment outcomes for head and neck mucosal melanoma (HNMM) patients seen at academic versus nonacademic centers and high versus low volume facilities.Study Design. Retrospective cohort study.Setting. National Cancer Database.Methods. Differences in treatment course and overall survival (OS) by facility type and volume were assessed for 2772 HNMM cases reported by the 2004 to 2017 National Cancer Database. A subgroup analysis was performed with a smaller cohort containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The association between academic facility and higher OS has been documented in several head and neck cancers. [59][60][61][62][63][64][65][66][67][68][69][70] Medicaid and nodal metastasis portended poorer OS, consistent with previously established prognostic factors in MSGC. [50][51][52][53][54][55] Surgical resection is the preferred definitive treatment of MSGC classified as cT4a or lower.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The association between academic facility and higher OS has been documented in several head and neck cancers. [59][60][61][62][63][64][65][66][67][68][69][70] Medicaid and nodal metastasis portended poorer OS, consistent with previously established prognostic factors in MSGC. [50][51][52][53][54][55] Surgical resection is the preferred definitive treatment of MSGC classified as cT4a or lower.…”
Section: Discussionsupporting
confidence: 85%
“…These factors are likely responsible for most patients (57.2%) with cT4b MSGC undergoing definitive treatment at academic facilities. The association between academic facility and higher OS has been documented in several head and neck cancers 59‐70 . Medicaid and nodal metastasis portended poorer OS, consistent with previously established prognostic factors in MSGC 50‐55 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Though it may not always be the case, academic centers are likely to encounter a higher volume of craniopharyngioma cases due to the complexity of their treatment, which typically includes surgical resection with the addition of chemotherapy and/or radiation. 7,23,24 This is due in part to the invasive nature of the tumor with involvement of nearby critical neurovascular and neuroendocrine structures. Surgical and adjuvant treatment planning is paramount for successful control of craniopharyngioma requiring collaboration by an expert multidisciplinary team and resources to treat these complex skull base lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that cancers with the greatest benefit from high-volume facilities were those with the highest number of cancer-related deaths, including cancers of the pancreas, esophagus, and brain ( 23 ). Select studies have shown poorer survival at large institutions, possibly due to the complexity of patients referred to and treated at these centers ( 24 ).…”
Section: Facility Type and Cancer Outcomes In The Usmentioning
confidence: 99%